2007
DOI: 10.1007/s10750-006-0459-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent high-biomass blooms of Alexandrium taylorii (Dinophyceae), a HAB species expanding in the Mediterranean

Abstract: Summer outbreaks of the dinoflagellate Alexandrium taylorii Balech are recurrent events in nearshore waters of Sicily (Italy)-a central region in the Mediterranean Sea-producing dense yellowish-green patches. Beyond the local phenomenon, the problem covers a broader geographic scale, involving also other European localities, mostly in Spain. Biological, environmental, and molecular data are reported here from a semi-closed bay of Sicily (Vulcano Island, Tyrrhenian Sea, 2000-2003), showing in summer the recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
1
11
0
3
Order By: Relevance
“…It should be noted that La Fosca and Vulcano beaches are situated in highly urbanized areas and Tarragona harbor receives freshwater inflows from the River Francolí. There were few cases of a potential nutrient limitation in these areas and the blooms were not conditioned by nutrients (Giacobbe et al 2004.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted that La Fosca and Vulcano beaches are situated in highly urbanized areas and Tarragona harbor receives freshwater inflows from the River Francolí. There were few cases of a potential nutrient limitation in these areas and the blooms were not conditioned by nutrients (Giacobbe et al 2004.…”
Section: Discussionmentioning
confidence: 89%
“…LBA that may have earlier placed faster evolving species basally (Kim et al, 2005;Leaw et al, 2005;Montresor et al, 2004;. Phylogenetic inferences based solely on 5.8S rDNA and ITS regions extenuate this problem (Giacobbe et al, 2007;Masseret et al, 2009;Penna et al, 2008). The Alexandrium ITS regions are difficult to align correctly, and are therefore more suited to species identification rather than phylogenetic inference e.g.…”
Section: Evolution Of the Alexandrium Cladementioning
confidence: 99%
“…Widespread blooms of Alexandrium catenella and A. taylori have been described over the last decade along the Spanish, French and Italian coasts (Giacobbe and Yang 1999;Vila et al 2001;Penna et al 2005). A. taylori can be found in the natural environment in high cell densities (>10 6 cells L −1 ; Garcés et al 1999;Penna et al 2002;Giacobbe et al 2007) and toxin production was demonstrated in vitro by Emura et al (2004) and in Malaysia waters (Lim et al 2005). …”
Section: Introductionmentioning
confidence: 99%